Risks of corruption to development - Chine, Fairouz; Souliman, Mohamad Abdel Monem Al-Sayed Abo; Chine, Noual; Chine, Saida; Mohamed, Trifa (The journal of contemporary issues in business and government, 2023)
The mechanisms of globalization have produced the tools, means and technological innovations that facilitated the forms of corruption, and what it also entails from the increased movement of economic activity and financial openness globally and locally, and the tendency to liberalize foreign and internal trade, and the related developments, which contributed to alleviating administrative and financial restrictions, and creating Damage to the economic structure of the state through wasting economic resources, increasing burdens on the public budget, reducing the efficiency of economic performance, or misdistributing resources, with the intent of achieving personal benefits, material or non-material, whether in kind or monetary, at the expense of the public interest. Opening channels to the emergence of many forms and forms of corruption, and thus the increased possibility of the spread of new forms of corruption, the most important of which is economic corruption. All this has led to the need for an international defense strategy against the forms and methods of corruption in institutions in general and banking in particular, linking international cooperation and regional and local coordination between the various concerned bodies economically, securely and politically, and declaring a real state of war waged by the regulatory and supervisory bodies in different countries, as well as entities The organization of development projects based on financing and lending from banking institutions in all its forms and forms against practices and forms of corruption in them.